Effect of exercise on pseudo dilution anemia in healthy male subjects. A comparative study. - Fazal, Amaila; Mirza, Faizan (International Journal of Endorsing Health Science Research, 2016)
Regular exercise is largely done to have maintained body shape and fitness. It exerts influence on almost all physiological and psychological parameters. One of these is dilutional anemia or sports anemia that is the initial adaptation of body to exercise. The aim of present study was to evaluate the extent of dilutional anemia in healthy males who have been exercising for past three years at least. Randomly selected 40 male subjects from gymnasiums of Karachi were recruited in the study. Peripheral blood was collected pre and post exercise, and tested for hematocrit, hemoglobin concentration and red blood cell count. Increased hemoglobin concentration was observed which is directly related to increased red blood cell count which is inversely proportional to blood plasma level. So, decreased plasma level is the possible cause that pseudo dilution anemia was not observed in males who have been regularly exercising for past three years.